Minor millets in Tamil Nadu, India: Local market participation, on-farm diversity and farmer welfare - Takeshima, Hiroyuki; Nagarajan, Latha (Cambridge University Press, 2012)
Although farmer market participation raises income, it often also reduces on-farm varietal diversity. However, for under-utilized crops like minor millets, market participation may actually encourage growers to increase on-farm diversity through better access to new varieties exchanged at local markets and higher returns from varieties already grown. We test this hypothesis in two different agro-ecological niches, the Plains and the Hills in southern India. Empirical results based on propensity score matching indicate that, in the less fertile dryland plains, market participation improved on-farm varietal diversity of minor millets and increased net revenues – albeit with insignificant welfare effects on farm households. On the other hand, in the fertile hill ecosystems, market development had no effect on varietal diversity. Insights from such a comparison could help design suitable policy interventions for on-farm conservation of under-utilized crops in their own agro-ecosystems through active stakeholder participation.